ÍNDICE DE CONFIANÇA DO EMPRESÁRIO VAREJISTA DE SANTA ROSA EM 2008 - Graef, Nelinho D.; Zamberlan, Luciano; Sparemberger, Ariosto; Büttenbender, Pedro L.; Wagner, Adriano; Becker, Joice T. (Salão do Conhecimento, 2013)
Resumo